Enhancing nursing education through the implementation of an unfolding case study: Addressing maternal substance use disorders via experiential learning. - Coleman, Rebecca; Snuggs, Barbora; Jones, Sharon (Clinical Simulation in Nursing, 2026)
• Curriculum integration —A four-semester Bachelor of Science in Nursing curriculum on maternal SUD uses unfolding case studies and standardized patients to build clinical competency. • Public health focus— Addresses the rising epidemic of substance use among pregnant women, now affecting 30% and contributing to increased neonatal opioid withdrawal. • Student confidence— Simulation-based learning improves nursing students' confidence and preparedness to care for mothers with SUD. Social determinants emphasis— Incorporates World Health Organization's social determinants of health to deepen understanding of health inequities and their impact on maternal outcomes. • Realistic scenarios— Case studies reflect real-world complexity, enhancing critical thinking and trauma-informed care skills. Excellence in high-impact practices and experiential learning is essential in nursing education, particularly when addressing complex and sensitive issues such as substance use disorders (SUDs) among pregnant women. This project integrates a maternal SUD curriculum into a Bachelor of Science in Nursing program using unfolding case studies and standardized patient simulations. With rising rates of illicit drug use among pregnant women and increased neonatal opioid withdrawal syndrome, nursing students must be prepared to deliver compassionate, evidence-based care. Spanning four semesters, the curriculum incorporates prework, postconferences, and reflective assessments to address stigma, trauma-informed care, and social determinants of health. This experiential approach enhances student confidence, critical thinking, and clinical decision-making in managing maternal SUD and improving outcomes for mothers and infants.